Principales inconvenientes en la comercialización de maíz amarillo duro en el Cantón Puebloviejo - Provincia de Los Ríos - Villalta Marmolejo, Félix Alexy (2019)
Corn is one of the main grains in Ecuador, as it has a vital meaning for indigenous peoples, in addition to being considered a generator of life, which makes it a fundamental element of identity for our ancestors. In the country this grain has been cultivated for centuries and is an important source of income for Ecuadorian families dedicated to agriculture. Hard yellow corn in Ecuador is one of the most important agricultural products of the national economy. It is the main raw material for the production of concentrated (balanced) foods for the animal industry, especially commercial poultry farming, which is one of the most dynamic activities in the agricultural sector. in Ecuador, an average of 717,940 tm of dry yellow corn and 43,284 tm of soft corn corn are produced annually, indicating that dry yellow corn has a highly polarized production in the Costa region and in the case of soft corn corn is highly polarized in The Sierra region. Agricultural marketing can be defined as a series of services involved in moving a product from the point of production to the point of consumption. Therefore, agricultural marketing includes a series of interconnected activities ranging from production planning, cultivation and harvesting, packaging, transport, storage, processing of agricultural and food products, to their distribution and sale